PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA PT DAMAI INDAH GOLF BUMI SERPONG DAMAI - Aulan Yestika Putri; Whina Ratnawati (Journal of Research and Publication Innovation, 2025)
This Research ains to determine the effect of leadership style and work environment on employee performance at PT Damai Indah Golf Bumi Serpong Damai.This research uses quantitative methods to research certain populations or samples, sampling is generally random and data analysis is quantitative/statistical. The results of this research found that partially leadership style and work environment had a positive and significant effect on workmorale.Leadership style is the quality and quantity of work results achieved by an employee in carrying out his duties in accordance with the responsibilities given tohim. In this case, the influence of a leader is very decisive, because to realize goals,the company needs to apply a leadership style or work pattern that is consistent with the work situation it faces. Apart from that, a leader in carrying out his duties must try to create and maintain good relationships with his subordinates so that they can work productively. In this way, company productivity can be indirectly increased. The success of a leader in his leadership style, where there are differences in behavior between individuals faced, will support the formation of aneffective leadership style.The purpose of this research is to determine the influence of leadership style and work environment on employee morale at PT Damai Indah Golf Bumi Serpong Damai. The population in this study were all employees of PT Damai Indah Golf Bumi Serpong Damai, totaling 50 employees. Determining the number of samplestaken as respondents using a saturated sample, namely using the entire populationas a sample. The data collection techniques used in this research were questionnaires and interviews. The analysis techniques used in this research are multiple linear regression analysis, classical assumptions, hypothesis testing, andcoefficient of determination.